Sleep disorders in Down syndrome: a systematic review - Santos, Ravenna Araújo; Costa, Lellis Henrique; Linhares, Rebeca Coêlho; Pradella-Hallinan, Márcia; Coelho, Fernando Morgadinho Santos; Oliveira, Giuliano da Paz (Arquivos de Neuro-Psiquiatria, 2022)
Background: Sleep disorders are commonly observed in children with Down syndrome (DS) and can lead to significant behavioral and cognitive morbidities in these individuals. Objective: To perform a systematic review evaluating sleep disorders in individuals with DS. Methods: Search strategies were based on combinations of keywords: “Down syndrome”; “trisomy 21”; “sleep disorders”; “dyssomnias”; “sleep apnea”; “obstructive”; “sleeplessness”; “insomnia”; “parasomnias”; and “excessive daytime sleepiness”. PubMed and Science Direct were used. Only original studies and retrospective reviews in English published between January 2011 and March 2021 were included. Results: 52 articles were included, most of them involving children and adolescents under 18 years of age. The main sleep disorder associated with DS was obstructive sleep apnea (OSA). Some studies reported the presence of cognitive dysfunction in patients with DS and sleep-disordered breathing, and few have been found about parasomnia, insomnia, and daytime sleepiness in these patients. Movement disorders and unusual postures during sleep may be related to disordered sleep breathing in DS. The main treatment options for OSA are continuous positive airway pressure therapy (CPAP), surgery, and weight control. Computational modeling associated with MRI has been used to plan surgical interventions in these patients. Conclusions: Individuals with DS are at high risk of developing sleep-related breathing disorders. The main sleep disorder associated with DS was OSA. The presence of sleep-disordered breathing contributes to a worsening of cognitive function in patients with DS.
Keywords: Down Syndrome; Sleep Wake Disorders; Sleep Apnea Syndromes